성인에서 대상포진 예방접종 후 눈을 침범한 안면대상포진, 수막염이 동시에 발생한 1예 - 최지호(Ji-Ho Choi); 안민(Min Ahn); 조남천(Nam Chun Cho); 유인천(In Cheon You) (Daihan angwa haghoi jabji, 2021)
목적: 대상포진 예방접종 후 눈 및 안면대상포진, 수막염이 발생한 증례를 보고하고자 한다. 증례요약: 60세 남자가 왼팔에 대상포진 예방접종 후 4일째부터 왼눈 가쪽과 왼쪽 이마에 물집성 발적이 나타나 항바이러스제를 투여하였으나 점차 수포가 더 많아지고 7일째에는 두통이 심해지며 코끝, 뺨, 입천장까지 물집이 생겨 내원하였다. 과거력상 6년 전 갑상샘암으로 갑상샘 절제 후 갑상선호르몬 제제를 복용 중이었다. 어릴 때 정확히 수두로 진단받은 건 아니지만 얼굴에 원형발적이 있었다고 하였다. 세극등현미경상 결막부종 및 충혈, 각막주변부에 거짓가지모양병변이 있었다. 전방염증은 없었다. 뇌자기공명영상에서 특이 소견은 없었으나 뇌척수액검사에서 바이러스 양성으로 항바이러스제를 투여받았다. Ganciclovir 연고, levofloxacin, bromfenac 을 점안하였고 1주일 후 거짓가지모양병변은 없어지고 결막부종도 호전되었다. 발생 후 6개월까지 재발은 없었다. 결론: 대상포진 예방접종 후 안면 또는 눈대상포진, 수막염의 활성화는 매우 드물지만 발생할 수 있으므로 주의해야 하고 발생 시 즉각적인 항바이러스 치료가 필요하다. Purpose: To report a case of ocular and facial herpes zoster and meningitis after herpes zoster vaccination. Case summary: A 60-year-old man was administered Zostavax® on his left arm; he developed a vesicular rash over his left eye and forehead 4 days afterwards. He started antiviral drugs for the rash, and visited the hospital for severe headache and spread of the rash to involve the tip of his nose, face, and palate by day 7. He was taking Synthyroid® (Bukwang Pharmaceuticals, Seoul, Korea) since his thyroidectomy for thyroid cancer 6 years ago. He had never been diagnosed with chickenpox, but had an episode of red facial rash in childhood. Slit-lamp examination revealed conjunctival chemosis, hyperemia, and a pseudodendrite in the peripheral cornea. The anterior chamber was quiet, and there were no significant findings on his brain magnetic resonance imaging. Varicella zoster virus was detected in the cerebrospinal fluid by polymerase chain reaction. The patient was treated with oral acyclovir drugs and topical ganciclovir, levofloxacin, and bromfenac. One week later, the pseudodendrite disappeared and conjunctival chemosis improved. There was no recurrence during 6 months follow-up. Conclusions: Reactivation of ocular or facial herpes zoster or meningitis after zoster vaccination may occur, rarely. Immediate antiviral treatment is required in these cases. KCI Citation Count: 0